Construct validation of a complete postpartum health and well-being patient reported outcome measure: prospective cohort studyAJOG Global Reports at a Glance - Laura J. O'Byrne, BMBS, MSc, PhD; Gillian M. Maher, PhD; Jill M. Mitchell, MB, BCh, BAO; Ali S Khashan, PhD; Richard M. Greene, MB, BCh, BAO; John P. Browne, PhD; Fergus P. McCarthy, MB, BCh, BAO, PhD (AJOG Global Reports)
ABSTRACT: Background: Despite a focus on patient-reported outcome measures (PROM) in maternity care, a standardized tool is lacking. Current existing measures often focus on a single dimension of postpartum health. Objective: This study evaluated the construct validity of using a suite of PROMs based on the top psychometrically validated tools available. They were combined to achieve coverage of all important aspects of postpartum well-being outlined by the International Consortium of Health Outcomes (ICHOM). Methods: Recruitment took place in a tertiary university maternity hospital between April 3rd 2023, and October 28th 2023, with final responses collected in January 2024. Postnatal women were recruited before hospital discharge and consented to completing the PROM tool which consisted of the Postpartum Quality of Life (PQoL) tool, the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) and 2 additional questions on pelvic pain with sexual intercourse. The PROM was administered at T1=first week postpartum, T2=6 weeks and T3=12 weeks postpartum. We evaluated the construct validity of these tools through hypothesis testing, proposing that: (1) the instrument should differentiate between groups with and without morbidity, (2) the instrument should differentiate between groups based on delivery type, and (3) should detect change over the postpartum period. Statistical analyses, including chi-square tests, repeated measures ANOVA, and independent t-tests, were used for data analysis. Results: 534 women were recruited, with an average age of 32 years (±5.0), 90.6% (n=484) had term deliveries, 59% (n=316) were multiparous, 40% (n=216) had spontaneous vaginal deliveries (SVD), 12% (n=63) had operative vaginal deliveries and 47.7% (n= 255) had caesarean sections. Examining the tools’ ability to detect changes based on morbidity found no significant differences in PQoL, ICIQ-UI SF or pelvic pain scores between groups with and without maternal morbidity. There were also no differences found in the scores of mothers who had babies admitted to the Neonatal Unit (NNU). Examining score differences based on delivery type, found no variations in total PQoL scores across all timepoints. There were no score differences at other time points in the ICIQ-UI SF or pelvic pain question scores. The PQoL, ICIQ-UI SF and the pelvic pain with sexual intercourse questions had statistically significant difference in their overall scores over the 3 timepoints of the study. The PQoL scores were T1: 128 [±9.67], T2: 125 [±8.47], and T3: 126 [±8.51] P=.002. The ICIQ-UI SF had a median score and interquartile ranges of T1: 7.7 (IQR=6), T2: 9 (IQR=7), and T3: 9 (IQR=7), P=<.001. The pelvic pain with intercourse questions median score was T1: 6 (IQR=2), T2: 5.5 (IQR=2) and T3: 4 (IQR=2), P=.4957. Conclusion: While this suite of PROMs demonstrated sensitivity in detecting changes in postpartum well-being over time, it did not consistently discern differences based on morbidity (maternal or neonatal) or on delivery type. These findings suggest the need for a more clinically relevant postpartum PROM.